ISOLATION AND NMR CHARACTERIZATION OF 3Β-HYDROXYHOPAN-13(12),22(29)-DIENE AND LUP-20(29)-EN-3-OL,3-HEXENOATE FROM COMBRETUM GRANDIFLORUM ROOT BARK AND MOLECULAR DOCKING EVALUATION OF THEIR ANTIMICROBIAL POTENTIAL - Obansa, Rukayya Muhammed; Ndukwe, George Ileogbulam; Habila, James Dama; Jimoh, Tajudeen Abdullahi; Uttu, Jubrin Ahmed (FUDMA JOURNAL OF SCIENCES, 2025)
Triterpenoids have shown various pharmacological effects, including antimicrobial, anticancer, and cardioprotective activities. Combretum grandiflorum has been traditionally used for its antioxidative and antimicrobial properties, however, its root bark remains underexplored as a source of bioactive compounds. This study, therefore, focused on isolating bioactive triterpenoids from Combretum grandiflorum root bark extract and assessing their antimicrobial potential. The powdered root bark was subjected to cold maceration using methanol as solvent and polarity dependent fractionation resulted to ethyl acetate fraction. The fraction was subjected to column chromatography, further purification led to the isolation of two compounds. Structural analysis of the compounds was conducted using Nuclear Magnetic Resonance (NMR) spectroscopy, and the results aligned with literature reports. This marks the first report of 3β-hydroxyHopan-13(12),22(29)-diene and Lup-20(29)-en-3-ol,3-hexenoate from C. grandiflorum. The antimicrobial potential of these compounds was further assessed using molecular docking approaches against Escherichia coli murein tripeptide amidase (PDB: 5HXD) and Candida albicans glutamate dehydrogenase (PDB: 7F77) which are critical for pathogen survival. Molecular docking simulations showed that compound 1 bound to Escherichia coli (PDB: 5HXD) and Candida albicans (PDB: 7F77) with binding energies of –8.8 and –7.6 kcal/mol, respectively. Compound 2 demonstrated affinities of –8.0 kcal/mol (E. coli) and –9.3 kcal/mol (C. albicans). This study confirms the presence 3β-hydroxyHopan-13(12),22(29)-diene and Lup-20(29)-en-3-ol,3-hexenoate triterpenoids in C. grandiflorum root bark and highlights their strong in silico interactions with microbial targets. These results suggest promising antimicrobial potential and warrant further in vitro and in vivo studies to experimentally validate their efficacy.